APLIKASI TIK TOK SEBAGAI MEDIA PEMBELAJARAN BAHASA BALI - I GEDE SUDIARTA (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
The development of learning media and the announcement of the industrial revolution 4.0 are expected to be published. Related to this, the dynamics of learning may no longer implement conventional methods, especially in the selection of learning media. Learning media in the all-digital era must continue to follow the direction of technological developments. Learning media must be interesting, creative, close and attached to students. The Tik Tok application is present in the midst of society, but in fact young people and even the elderly really enjoy this application. Based on this statement, it can be concluded that if used and mediated properly, this Tik Tok application will become an interesting learning media creative as well as fun. The use of the Tik Tok application as an interactive learning medium is expected to help students understand and accept the learning process carried out by the teacher. Interactive learning media can represent what the teacher has not been able to convey and also in the learning process it will be much more effective and efficient. Through this Tik Tok application, a teacher can easily create interactive learning, so that it can adapt to the environmental situation and conditions of students.